2007
DOI: 10.1111/j.1365-3016.2007.00782_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Is low birthweight associated with dental caries in permanent dentition?

Abstract: The aim of this study was to test the hypothesis of association between low birthweight and dental caries. This study used data from the Third National Health and Nutritional Examination Survey, 1988-94 (NHANES III) including 7- to 11-year-old children with complete dental caries information (n = 2439). Two case definitions for dental caries were used: presence of the disease in more than one tooth, and more than 10% of teeth with dental caries. Low birthweight was defined as those children born weighing <2500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
(52 reference statements)
2
19
0
5
Order By: Relevance
“…Pois, em um estudo longitudinal realizado anteriormente 17 , foi observado que crianças com baixo peso aos 12 meses, sem especificação de prematuridade, apresentaram maior risco de ter alto índice de cárie. Resultados divergentes foram obtidos por Saraiva et al 18 (2007), pois não encontraram associação estatística entre peso no nascimento e CPOD na faixa etária dos sete aos 11 anos de idade, porém os dados de peso ao nascimento desse estudo foram obtidos por meio de questionário respondido pelo responsável no momento do estudo, enquanto no desenho de estudo realizado por Peres et al 15 (2005), o peso foi obtido por pesagem da criança, o que seria mais confiável.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Pois, em um estudo longitudinal realizado anteriormente 17 , foi observado que crianças com baixo peso aos 12 meses, sem especificação de prematuridade, apresentaram maior risco de ter alto índice de cárie. Resultados divergentes foram obtidos por Saraiva et al 18 (2007), pois não encontraram associação estatística entre peso no nascimento e CPOD na faixa etária dos sete aos 11 anos de idade, porém os dados de peso ao nascimento desse estudo foram obtidos por meio de questionário respondido pelo responsável no momento do estudo, enquanto no desenho de estudo realizado por Peres et al 15 (2005), o peso foi obtido por pesagem da criança, o que seria mais confiável.…”
Section: Discussionunclassified
“…Observou-se que as crianças abaixo do peso aos 12 meses apresentaram chance (OR) 4,1 vezes maior de apresentar alto índice de cárie 17 . Entretanto, Saraiva et al 18 (2007) também tiveram como objetivo avaliar a associação entre baixo peso ao nascimento, segundo relato da mãe em questionário, e CPOD aos sete e 11 anos de idade, porém, os autores não encontraram correlação estatística. Esses resultados também corroboram o estudo transversal realizado com 80 crianças que nasceram prematuras no Hospital Regional da Asa Sul (HRAS) de Brasília, no qual os autores concluíram que a prematuridade não é um fator predisponente para cárie 19 .…”
Section: Componentes Biológicosunclassified
“…This finding was in line with that of Javadi Nejad et al (18) who evaluated 100 children of 3 and 4 years and found a relationship between high DMFT and low birth weight. Biologic justification for the possible association between low birth weight and dental caries might be attributed to disruptions in development and maturation of enamel structures, which can lead to increased enamel defects due to pre-birth calcium deficiency and physiological stresses (7,15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated low birth weight and preterm birth as predisposing factors for the development of caries. Low birth weight is suggested to perhaps be associated with enamel defects such as hypomineralization and hypoplasia, possibly causing facilitation of streptococci mutans colonization and increases in dental plaque (7), which can destroy enamel structure (15). Nevertheless, previous studies are highly controversial.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation